Promoting the comprehension of additive composition by deaf children - Nunes, T; Bryant, P; Evans, D; Bell, D; Hallett, D (2013)
This study aims at analyzing the comprehension of additive composition of number by deaf children. This article describes two studies that use the Purchasing Task from Nunes and Schliemann (1990) to investigate the perception of additive composition by children in the context of counting money. In the first study, we compared the comprehension of the concept by deaf children and hearing children of the same age. In the second study, we carried out a brief intervention to evaluate the possibility of enhancing deaf children's apprehension of the concept. We concluded that the interventions, even brief ones, but theoretically meaningful and clearly directed, can be used to improve the performance of deaf children in tasks that evaluate additive composition.